I’jaz ‘Ilmy Al-Qur’ān dalam Penggunaan Kata Sama’ dan Baṣar - Anzah Muhimmatul Iliyya (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2020)
This article explaines the i’jaz ‘ilmy of al-Qur’ān in the use of the words sama’ and baṣar. The Qur’an often mentions these two words together in one verse, but what often comes first is the words sama’. This paper wants to know the secret behind the formation of those words using qualitative method, namely collecting data about the object of research in the form of the words sama’ and baṣar. Based on the research conducted, several conclusions have been found that the words sama’ and baṣar in the Qur’an are mentioned thirty-four times, although in some verses the words baṣar takes precedence, but does not change the consistency of the Qur’an in terms of balaghah and its contents. The consistency of al-Qur’an in the mention of the words sama’ which proves first proves that the phenomena that occur in the universe are true, the sense of hearing, especially in humans, is indeed more important than ever since being born into the world until it ends from the world. The words sama’ and baṣar in the form of singular always discuss the individual human responsibility in the hereafter. In addition, it was found that the words sama’ in the form of singular and baṣar in the plural which discusses the signs of God’s power in the world.